Producing Knowledge in Struggle: Introduction to Dividing Lines, Part II. (24th January 2023) - Gayle, Steven D.; Benjamin, Jesse
Abstract : This essay discusses the cultural work and practice behind this special issue, and the processes and specific institutionalities that had to be navigated in order to bring this project forward. We address the relative absence of spaces for discussion and consideration of Afro-Indigenous histories, cultures, intersections, and provide a preview of the contributors to this Part II of the Dividing Lines project.